Frequency Dependent Negative Dielectric Behavior in Parylene C Based Composite Films - Guduloglu, Utku; Kurnaz, Sedat; Seydioglu, Turgay; Bekar, Gizem; Ozturk, Ozgur (Prensip Publishing, 2024)
Dielectric materials are an important research topic for many applications today. Polymers are among the prominent dielectrics due to their durability, high ionic conductivity and low dielectric losses. This study investigates the dielectric properties of Parylene C (PAC)-based composite films. Capacitance and dissipation factor values are measured. Dielectric permittivity and losses are calculated. Negative capacitance and negative dielectric constant are observed, and resonant frequency values are compared. Activated carbon doping significantly impacts the resonant frequencies of the films. Doped samples exhibit higher positive and negative resonant frequencies (2.2560 MHz and 2.2593 MHz) compared to undoped counterparts (2.1952 MHz and 2.2015 MHz). Polarization further increases resonant frequencies, alongside dielectric permittivity and dissipation factor with permittivity experiencing a more pronounced increase. Post-polarization, doped samples display resonant frequencies of 2.3727 MHz and 2.3761 MHz, while undoped samples reach 2.3658 MHz and 2.3727 MHz. A comprehensive analysis of impedance, resistance, and reactance values reveals insights into the composite film's behavior. Crucially, throughout the measurements, the composite films display a consistent inductive response at frequencies above their resonance frequencies. Understanding the mechanisms behind this inductive response could open up new possibilities for the use of these films in advanced electronic devices and circuits.